Case Report: The Effect of Craniosacral Techniques on Chronic Headache - Mohammad Reza Nourbakhsh; Bashari Hatef (University of Social Welfare and Rehabilitation Sciences, 2002)
The purpose of this study was to assess the effect of Craniosacral techniques on chronic headache. We used an A-B-A single subject design which consisted of one week of baseline (pretreatment), four weeks of treatment, and follow up period. The subject of this study was a 47 years old female who complained of severe headache during the last five years. Patient had received multiple medical and physical therapy treatments without success. Began starting Craniosacral therapy. After treatment patient's headache decreased from 7.5 to 1 (0-10 scale), and her sleep disorder improved by 50% and the vertigo and tinnitus that patient complained removed. Although this study showed the positive effect of Craniosacral techniques on chronic headache in a single subject, more studies are needed in this area.